Otonomi Daerah Khusus Aceh: Jembatan menuju Rekonsiliasi atau Sumber Ketegangan Baru - A Rahman, Dahlan; bin Abubakar, Muhammad; Rizwan, Muhammad; Muntasir, Muntasir; Hidayat, Bimby (Universitas Indo Global Mandiri, 2024)
This article aims to explore whether Aceh's special autonomy has served more as a bridge to reconciliation or as a source of new tensions in the region. The article will examine various aspects of the implementation of special autonomy in Aceh, including the political, social and economic dynamics that accompanied it. The research uses a qualitative approach with a case study method. Through a comprehensive analysis, it is found that Aceh's special autonomy is a complex concept with various accompanying dynamics. On the one hand, special autonomy can serve as a bridge to reconciliation by providing space for the people of Aceh to express their identity and be involved in decision-making processes. However, on the other hand, special autonomy can also be a source of new tensions due to different interpretations of authority, conflicts of interest among local elites, and unresolved welfare issues. The challenges and dynamics of special autonomy in Aceh after the Helsinki MoU demonstrate the complexity of the situation faced by the province. While there are challenges in implementing special autonomy, there are also opportunities to strengthen democratic processes, economic empowerment, and socio-cultural integration in Aceh.